Arsenic-poisoning-resistant denitration catalyst with core-shell structure and preparation method thereof
Patent Information
- Application Number
- CN202410633461.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-21
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2044-05-21
AI Technical Summary
催化剂的活性下降将会对脱硝系统及下游设备的运行造成不良影响,甚至会导致NOx超标排放
[0020] (1) The present invention constructs a composite oxide denitration catalyst with a double core-shell structure by self-assembly method. The double core-shell structure is constructed into a three-dimensional network morphology, which greatly reduces the adsorption, oxidation and deposition of arsenic on the catalyst surface.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to the field of denitrification catalyst technology, and in particular to a core-shell structured denitrification catalyst resistant to arsenic poisoning and its preparation method. Background Technology
[0002] In practical applications of denitrification catalysts, arsenic poisoning is one of the main causes of SCR denitrification catalyst deactivation. The primary reason is that As₂O₃(g) diffuses into the catalyst through adsorption, clogging the catalyst pores and preventing nitrogen oxides and ammonia in the flue gas from reaching the catalytic active sites, leading to catalyst poisoning and deactivation. Simultaneously, As₂O₃(g) adsorbed on both active and inactive sites on the catalyst surface undergoes catalytic oxidation to form As₂O₅. As₂O₅ forms a protective layer on the catalyst surface, hindering the adsorption of ammonia and nitrogen oxides, thus reducing the catalyst's denitrification efficiency. If the mass fraction of arsenic in the coal exceeds 3 × 10⁻⁶, further denitrification will occur. -6 The lifespan of SCR catalysts will decrease by approximately 30%. This decline in catalyst activity will adversely affect the operation of denitrification systems and downstream equipment, and may even lead to excessive NOx emissions. Therefore, developing denitrification catalysts with synergistic anti-arsenic poisoning properties is of great significance. Summary of the Invention
[0003] The purpose of this invention is to provide a core-shell structured anti-arsenic poisoning denitrification catalyst and its preparation method, which can solve the above-mentioned technical problems.
[0004] This invention provides a core-shell structured anti-arsenic poisoning denitrification catalyst, which uses vanadium-molybdenum-holmium-zinc composite oxide particles as the core, silicon-cerium oxide as the inner shell, and titanium-phosphorus oxide as the outer shell. The mass ratio of the core to the inner shell is (3-15):100, and the mass ratio of the core to the outer shell is (25-60):100.
[0005] Preferably, the mass ratio of vanadium(+5) oxide, molybdenum(+6) oxide, holmium(+3) oxide, and zinc(+2) oxide in the vanadium-molybdenum-holmium-zinc composite oxide particles is 1:(2-10):(0.5-2):(0.1-1).
[0006] Preferably, the mass ratio of silicon oxide to cerium oxide in the silicon cerium oxide is 100:(1-10).
[0007] Preferably, the mass ratio of titanium oxide to phosphorus oxide in the titanium-phosphorus oxide is 100:(0.1-3).
[0008] This invention also provides a method for preparing the above-mentioned core-shell structured arsenic poisoning denitrification catalyst, comprising the following steps:
[0009] Step S1: Mix vanadium oxysulfate, ammonium molybdate, holmium sulfate, zinc sulfate and oxalic acid solution evenly to form solution A; place solution A in a high-pressure reactor lined with polytetrafluoroethylene, add dimethicone, and carry out hydrothermal reaction. After the reaction, the product is filtered, washed, vacuum dried and calcined to obtain vanadium-molybdenum-holmium-zinc composite oxide particles.
[0010] Step S2: Vanadium-molybdenum-holmium-zinc composite oxide particles, acrylic vinyl pyridine copolymer, and deionized water are ultrasonically stirred for 12-24 hours to obtain suspension A. Suspension A is filtered to obtain activated vanadium-molybdenum-holmium-zinc composite oxide particles.
[0011] Step S3: The activated vanadium-molybdenum-holmium-zinc composite oxide particles are ultrasonically dispersed in glycerol to form suspension B. The silicon-cerium sol is added to suspension B and ultrasonically dispersed for 2-6 hours to form suspension C. Urea solution is added dropwise to suspension C until a precipitate is formed. The solution is stirred evenly to obtain solution D under critical conditions.
[0012] Step S4: Add propylene glycol block polyether type L-62 to titanium phosphate sol, add urea solution until a precipitate is formed in the solution, stir evenly, and obtain solution E under critical conditions;
[0013] Step S5: Add solution E to solution D, stir evenly, and add to a high-pressure reactor lined with polytetrafluoroethylene for hydrothermal reaction. After the reaction, the product is filtered, washed, vacuum dried, and calcined to obtain a double-core-shell structured anti-arsenic poisoning denitrification catalyst.
[0014] Preferably, in step S1, the concentration of oxalic acid is 1%-5%, and the mass ratio of vanadium oxysulfate to dimethicone is 1:(0.1-0.5).
[0015] Preferably, in step S1, the hydrothermal reaction temperature is 150-200℃, the hydrothermal time is 6-15h, the drying temperature is 50-80℃, the drying time is 12-24h, the calcination temperature is 500-650℃, and the calcination time is 2-6h.
[0016] Preferably, in step S2, the mass ratio of vanadium oxide to vinylpyridine acrylate copolymer is 1:(0.1-0.5).
[0017] Preferably, in step S4, the mass ratio of vanadium oxide to propylene glycol block polyether is 1:(0.6-1.2).
[0018] Preferably, in step S5, the hydrothermal reaction temperature is 80-120℃ and the hydrothermal time is 8-12h; the drying temperature is 60-120℃ and the drying time is 24-48h; the calcination temperature is 450-600℃ and the calcination time is 3-8h.
[0019] Beneficial effects:
[0020] (1) The present invention constructs a composite oxide denitration catalyst with a double core-shell structure by self-assembly method. The double core-shell structure is constructed into a three-dimensional network morphology, which greatly reduces the adsorption, oxidation and deposition of arsenic on the catalyst surface.
[0021] (2) In this invention, holmium zinc can preferentially fix arsenic and inhibit the poisoning of other active components by arsenic;
[0022] (3) In this invention, the outer shell can effectively inhibit the adsorption of SO2 on the catalyst surface, and the inner shell can effectively inhibit the oxidation of SO2 on the catalyst surface, so that the catalyst maintains a low SO2 oxidation efficiency.
[0023] (4) The effective ratio of vanadium, molybdenum, holmium and zinc in this invention can efficiently adsorb and oxidize dioxins, achieving the purpose of synergistic removal;
[0024] (5) Compared with the prior art, the present invention can effectively inhibit the poisoning of catalyst by arsenic, synergistically remove dioxins, reduce SO2 / SO3 oxidation rate, maintain excellent denitrification activity for a long time in complex flue gas environment, and can be widely used in coal-fired power plants, waste power plants, steel industry, etc. Detailed Implementation
[0025] It should be noted that the following detailed descriptions are illustrative and intended to provide further explanation of this application. Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains.
[0026] It should be noted that the terminology used herein is for the purpose of describing particular implementations only and is not intended to limit the exemplary implementations according to this application. As used herein, the singular form includes the plural form unless the context clearly indicates otherwise. Furthermore, it should be understood that when the terms "comprising" and / or "including" are used in this description, they indicate the presence of features, steps, operations, devices, components, and / or combinations thereof.
[0027] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0028] The vanadium oxide, molybdenum oxide, holmium oxide, and zinc oxide mentioned below are pentavalent vanadium oxide, hexavalent molybdenum oxide, trivalent holmium oxide, and divalent zinc oxide, respectively.
[0029] Example 1
[0030] A core-shell structured denitrification catalyst for arsenic poisoning resistance comprises vanadium-molybdenum-holmium-zinc composite oxide particles as the core, silicon-cerium oxide as the inner shell, and titanium-phosphorus oxide as the outer shell. The mass ratio of the core to the inner shell is 8:100, and the mass ratio of the core to the outer shell is 35:100. The mass ratio of vanadium oxide, molybdenum oxide, holmium oxide, and zinc oxide in the vanadium-molybdenum-holmium-zinc composite oxide particles is 1:6:1.2:0.6. The mass ratio of silicon oxide to cerium oxide in the silicon-cerium oxide in the inner shell is 100:6. The mass ratio of titanium oxide to phosphorus oxide in the titanium-phosphorus oxide in the outer shell is 100:2.
[0031] The preparation method of the above-mentioned core-shell structured anti-arsenic poisoning denitration catalyst includes the following steps:
[0032] (1) Vanadium oxysulfate, ammonium molybdate, holmium sulfate, zinc sulfate, and 1% oxalic acid solution were mixed evenly to form solution A; solution A was placed in a high-pressure reactor lined with polytetrafluoroethylene, and dimethicone was added (the mass ratio of vanadium oxysulfate to dimethicone was 1:0.3), and a hydrothermal reaction was carried out. After the reaction, the product was filtered, washed, vacuum dried, and calcined to obtain vanadium-molybdenum-holmium-zinc composite oxide particles; wherein the hydrothermal reaction temperature was 185℃, the hydrothermal time was 12h; the drying temperature was 65℃, the drying time was 18h; and the calcination temperature was 550℃, the calcination time was 4h.
[0033] (2) Vanadium-molybdenum-holmium-zinc composite oxide particles, vinyl pyridine acrylic acid copolymer (vanadium oxide: propylene glycol block polyether mass ratio of 1:0.3) and deionized water were ultrasonically stirred for 18h to obtain suspension A. Filter suspension A to obtain activated vanadium-molybdenum-holmium-zinc composite oxide particles.
[0034] (3) The activated vanadium-molybdenum-holmium-zinc composite oxide particles were ultrasonically dispersed in glycerol to form suspension B. The cerium silicate sol (solution G1 was prepared by adding ethyl silicate to anhydrous ethanol, and solution G2 was prepared by adding acetic acid solution to cerium nitrate solution, and G2 was slowly added to G1, stirred evenly, and allowed to stand to obtain cerium silicate sol; other examples below have related sols, and all of them use this method) was added to suspension B. After ultrasonic dispersion for 3.5 h, suspension C was formed. Urea solution was added dropwise to suspension C until a precipitate was formed in the solution. The solution was stirred evenly to obtain solution D in the critical state.
[0035] (4) Propylene glycol block polyether L-62 type (the mass ratio of vanadium oxide to propylene glycol block polyether is 1:0.9) is added to titanium phosphate sol (the solution H1 is prepared by adding tetrabutyl titanate to anhydrous ethanol, dilute phosphoric acid is added to solution H1, stirred evenly, and allowed to stand to obtain titanium phosphate sol. Other examples below have related sols, and this method is used in all of them), urea solution is added until a precipitate is formed in the solution, stirred evenly, and aged for 16 hours to obtain solution E under critical conditions.
[0036] (5) Add solution E to solution D, stir evenly, and add it to a high pressure vessel lined with polytetrafluoroethylene. The hydrothermal reaction temperature is 100℃ and the hydrothermal time is 10h; the drying temperature is 85℃ and the drying time is 36h; the calcination temperature is 550℃ and the calcination time is 6h, thus obtaining a double-layer core-shell structure anti-arsenic poisoning denitrification catalyst.
[0037] Example 2
[0038] A core-shell structured denitrification catalyst for arsenic poisoning resistance comprises vanadium-molybdenum-holmium-zinc composite oxide particles as the core, silicon-cerium oxide as the inner shell, and titanium-phosphorus oxide as the outer shell. The mass ratio of the core to the inner shell is 3:100, and the mass ratio of the core to the outer shell is 25:100. The mass ratio of vanadium oxide, molybdenum oxide, holmium oxide, and zinc oxide in the vanadium-molybdenum-holmium-zinc composite oxide particles is 1:2:0.5:0.1. The mass ratio of silicon oxide to cerium oxide in the silicon-cerium oxide in the inner shell is 100:1. The mass ratio of titanium oxide to phosphorus oxide in the titanium-phosphorus oxide in the outer shell is 100:0.1.
[0039] The preparation method of the above-mentioned core-shell structured anti-arsenic poisoning denitration catalyst includes the following steps:
[0040] (1) Vanadium oxysulfate, ammonium molybdate, holmium sulfate, zinc sulfate, and 1% oxalic acid solution were mixed evenly to form solution A; solution A was placed in a high-pressure reactor lined with polytetrafluoroethylene, and dimethicone was added (the mass ratio of vanadium oxysulfate to dimethicone was 1:0.1), and a hydrothermal reaction was carried out. After the reaction, the product was filtered, washed, vacuum dried, and calcined to obtain vanadium-molybdenum-holmium-zinc composite oxide particles; wherein the hydrothermal reaction temperature was 150℃, the hydrothermal time was 6h; the drying temperature was 50℃, the drying time was 12h; and the calcination temperature was 500℃, the calcination time was 2h.
[0041] (2) Vanadium-molybdenum-holmium-zinc composite oxide particles, vinyl pyridine acrylic acid copolymer (vanadium oxide: propylene glycol block polyether mass ratio of 1:0.1) and deionized water were ultrasonically stirred for 12 h to obtain suspension A. Filter suspension A to obtain activated vanadium-molybdenum-holmium-zinc composite oxide particles.
[0042] (3) The activated vanadium-molybdenum-holmium-zinc composite oxide particles were ultrasonically dispersed in glycerol to form suspension B. The silicon-cerium sol was added to suspension B and ultrasonically dispersed for 2 hours to form suspension C. Urea solution was added dropwise to suspension C until a precipitate was formed. The solution was stirred evenly to obtain solution D under critical conditions.
[0043] (4) Add propylene glycol block polyether type L-62 (vanadium oxide: propylene glycol block polyether mass ratio of 1:0.6) to titanium phosphate sol, add urea solution until a precipitate is formed in the solution, stir evenly, and age for 8 hours to obtain solution E under critical conditions.
[0044] (5) Add solution E to solution D, stir evenly, and add it to a high pressure vessel with a polytetrafluoroethylene liner. The hydrothermal reaction temperature is 80℃ and the hydrothermal time is 8h; the drying temperature is 60℃ and the drying time is 24h; the calcination temperature is 450℃ and the calcination time is 3h, thus obtaining a double-layer core-shell structure anti-arsenic poisoning denitrification catalyst.
[0045] Example 3
[0046] A core-shell structured denitrification catalyst for arsenic poisoning resistance comprises vanadium-molybdenum-holmium-zinc composite oxide particles as the core, silicon-cerium oxide as the inner shell, and titanium-phosphorus oxide as the outer shell. The mass ratio of the core to the inner shell is 15:100, and the mass ratio of the core to the outer shell is 60:100. The mass ratio of vanadium oxide, molybdenum oxide, holmium oxide, and zinc oxide in the vanadium-molybdenum-holmium-zinc composite oxide particles in the core is 1:10:2:1. The mass ratio of silicon oxide to cerium oxide in the silicon-cerium oxide in the inner shell is 100:10. The mass ratio of titanium oxide to phosphorus oxide in the titanium-phosphorus oxide in the outer shell is 100:3.
[0047] The preparation method of the above-mentioned core-shell structured anti-arsenic poisoning denitration catalyst includes the following steps:
[0048] (1) Vanadium oxysulfate, ammonium molybdate, holmium sulfate, zinc sulfate, and 1% oxalic acid solution were mixed evenly to form solution A; solution A was placed in a high-pressure reactor lined with polytetrafluoroethylene, and dimethicone was added (the mass ratio of vanadium oxysulfate to dimethicone was 1:0.5), and a hydrothermal reaction was carried out. After the reaction, the product was filtered, washed, vacuum dried, and calcined to obtain vanadium-molybdenum-holmium-zinc composite oxide particles; wherein the hydrothermal reaction temperature was 200℃, the hydrothermal time was 15h; the drying temperature was 80℃, the drying time was 24h; and the calcination temperature was 650℃, the calcination time was 6h.
[0049] (2) Vanadium-molybdenum-holmium-zinc composite oxide particles, vinyl pyridine copolymer of acrylate (vanadium oxide: propylene glycol block polyether mass ratio of 1:0.5) and deionized water were ultrasonically stirred for 24 h to obtain suspension A. Filter suspension A to obtain activated vanadium-molybdenum-holmium-zinc composite oxide particles.
[0050] (3) The activated vanadium-molybdenum-holmium-zinc composite oxide particles were ultrasonically dispersed in glycerol to form suspension B. The silicon-cerium sol was added to suspension B and ultrasonically dispersed for 6 hours to form suspension C. Urea solution was added dropwise to suspension C until a precipitate was formed. The solution was stirred evenly to obtain solution D under critical conditions.
[0051] (4) Add propylene glycol block polyether type L-62 (vanadium oxide: propylene glycol block polyether mass ratio of 1:1.2) to titanium phosphate sol, add urea solution until a precipitate is formed in the solution, stir evenly, and age for 24 hours to obtain solution E under critical conditions.
[0052] (5) Add solution E to solution D, stir evenly, and add it to a high pressure vessel with a polytetrafluoroethylene liner. The hydrothermal reaction temperature is 120℃ and the hydrothermal time is 12h; the drying temperature is 120℃ and the drying time is 48h; the calcination temperature is 600℃ and the calcination time is 8h, thus obtaining a double-layer core-shell structure anti-arsenic poisoning denitrification catalyst.
[0053] Example 4
[0054] A core-shell structured denitrification catalyst for arsenic poisoning resistance comprises vanadium-molybdenum-holmium-zinc composite oxide particles as the core, silicon-cerium oxide as the inner shell, and titanium-phosphorus oxide as the outer shell. The mass ratio of the core to the inner shell is 4:100, and the mass ratio of the core to the outer shell is 35:100. The mass ratio of vanadium oxide, molybdenum oxide, holmium oxide, and zinc oxide in the vanadium-molybdenum-holmium-zinc composite oxide particles is 1:6:1:0.3. The mass ratio of silicon oxide to cerium oxide in the silicon-cerium oxide in the inner shell is 100:3. The mass ratio of titanium oxide to phosphorus oxide in the titanium-phosphorus oxide in the outer shell is 100:1.5.
[0055] The preparation method of the above-mentioned core-shell structured anti-arsenic poisoning denitration catalyst includes the following steps:
[0056] (1) Vanadium oxysulfate, ammonium molybdate, holmium sulfate, zinc sulfate and 1% oxalic acid solution were mixed evenly to form solution A; solution A was placed in a high-pressure reactor lined with polytetrafluoroethylene, dimethicone was added, and a hydrothermal reaction was carried out. After the reaction, the product was filtered, washed, vacuum dried and calcined to obtain vanadium-molybdenum-holmium-zinc composite oxide particles; wherein the hydrothermal reaction temperature was 175℃ and the hydrothermal time was 11h; the drying temperature was 65℃ and the drying time was 20h; the calcination temperature was 630℃ and the calcination time was 3h.
[0057] (2) Vanadium-molybdenum-holmium-zinc composite oxide particles, acrylic vinyl pyridine copolymer, and deionized water were ultrasonically stirred for 18 hours to obtain suspension A. Suspension A was filtered to obtain activated vanadium-molybdenum-holmium-zinc composite oxide particles.
[0058] (3) The activated vanadium-molybdenum-holmium-zinc composite oxide particles were ultrasonically dispersed in glycerol to form suspension B. The silicon-cerium sol was added to suspension B and ultrasonically dispersed for 4 hours to form suspension C. Urea solution was added dropwise to suspension C until a precipitate was formed. The solution was stirred evenly to obtain solution D under critical conditions.
[0059] (4) Add propylene glycol block polyether type L-62 to titanium phosphate sol, add urea solution until a precipitate is formed in the solution, stir evenly, and age for 15 hours to obtain solution E under critical conditions.
[0060] (5) Add solution E to solution D, stir evenly, and add to a high pressure vessel with a polytetrafluoroethylene liner. The hydrothermal reaction temperature is 110℃ and the hydrothermal time is 7h; the drying temperature is 95℃ and the drying time is 32h; the calcination temperature is 600℃ and the calcination time is 3.5h to obtain a double-layer core-shell structure anti-arsenic poisoning denitrification catalyst.
[0061] Example 5
[0062] A core-shell structured denitrification catalyst for arsenic poisoning resistance comprises vanadium-molybdenum-holmium-zinc composite oxide particles as the core, silicon-cerium oxide as the inner shell, and titanium-phosphorus oxide as the outer shell. The mass ratio of the core to the inner shell is 12:100, and the mass ratio of the core to the outer shell is 55:100. The mass ratio of vanadium oxide, molybdenum oxide, holmium oxide, and zinc oxide in the vanadium-molybdenum-holmium-zinc composite oxide particles is 1:3:2:0.6. The mass ratio of silicon oxide to cerium oxide in the silicon-cerium oxide in the inner shell is 100:3. The mass ratio of titanium oxide to phosphorus oxide in the titanium-phosphorus oxide in the outer shell is 100:1.5.
[0063] The preparation method of the above-mentioned core-shell structured anti-arsenic poisoning denitration catalyst includes the following steps:
[0064] (1) Vanadium oxysulfate, ammonium molybdate, holmium sulfate, zinc sulfate and 1% oxalic acid solution were mixed evenly to form solution A; solution A was placed in a high-pressure reactor lined with polytetrafluoroethylene, dimethicone was added, and a hydrothermal reaction was carried out. After the reaction, the product was filtered, washed, vacuum dried and calcined to obtain vanadium-molybdenum-holmium-zinc composite oxide particles; wherein the hydrothermal reaction temperature was 175℃ and the hydrothermal time was 13h; the drying temperature was 75℃ and the drying time was 18h; the calcination temperature was 630℃ and the calcination time was 4.5h.
[0065] (2) Vanadium-molybdenum-holmium-zinc composite oxide particles, vinyl pyridine copolymer of acrylic acid, and deionized water were ultrasonically stirred for 14 hours to obtain suspension A. Suspension A was filtered to obtain activated vanadium-molybdenum-holmium-zinc composite oxide particles.
[0066] (3) The activated vanadium-molybdenum-holmium-zinc composite oxide particles were ultrasonically dispersed in glycerol to form suspension B. The silicon-cerium sol was added to suspension B and ultrasonically dispersed for 4 hours to form suspension C. Urea solution was added dropwise to suspension C until a precipitate was formed. The solution was stirred evenly to obtain solution D under critical conditions.
[0067] (4) Add propylene glycol block polyether type L-62 to titanium phosphate sol, add urea solution until a precipitate is formed in the solution, stir evenly, and age for 22 hours to obtain solution E under critical conditions.
[0068] (5) Add solution E to solution D, stir evenly, and add to a high pressure vessel lined with polytetrafluoroethylene. The hydrothermal reaction temperature is 85℃ and the hydrothermal time is 10h; the drying temperature is 85℃ and the drying time is 32h; the calcination temperature is 600℃ and the calcination time is 3.5h to obtain a double-layer core-shell structure anti-arsenic poisoning denitrification catalyst.
[0069] Compare with Example 1
[0070] An anti-arsenic poisoning denitrification catalyst, compared with Example 1, does not have a shell structure (i.e., it does not use silicon cerium oxide as the inner shell and titanium phosphorus oxide as the outer shell), but the rest of the formulation and preparation method are the same as in Example 1.
[0071] Compare with Example 2:
[0072] An anti-arsenic poisoning denitrification catalyst, compared with Example 1, uses only titanium phosphorus oxide as the outer shell, while the rest of the formulation and preparation method are the same as in Example 1.
[0073] Compare with Example 3:
[0074] An anti-arsenic poisoning denitrification catalyst, compared with Example 1, uses only silicon cerium oxide as the outer shell, while the rest of the formulation and preparation method are the same as in Example 1.
[0075] Compare with Example 4:
[0076] An anti-arsenic poisoning denitrification catalyst, compared with Example 1, removes holmium oxide and zinc oxide from the vanadium-molybdenum-holmium-zinc composite oxide particles, while the rest of the formulation and preparation method are the same as in Example 1.
[0077] To investigate the activity of the denitrification catalysts prepared in the above examples and control examples, their denitrification efficiency was tested at flue gas temperatures of 200-450℃. The test results are shown in Table 1.
[0078] The test conditions are as follows: test temperature 250-450℃, NH3 volume concentration 500ppm, dioxin (simulated test using chlorobenzene) volume concentration 500ppm, NH3 / NO = 1, GHSV = 120000h. -1 Table 1 shows the denitrification efficiency of different denitrification catalysts.
[0079] Table 1 Catalyst Denitrification Efficiency
[0080]
[0081] As shown in Table 1, the arsenic poisoning-resistant denitrification catalyst prepared by the method of the present invention has high denitrification efficiency and excellent denitrification performance in the temperature range of 200-500℃.
[0082] To investigate the denitrification activity (1.2% As2O3 loaded), catalyst surface area and As2O3 deposition amount, and N2 selectivity of the above-mentioned examples and control examples at 350℃, the test results are shown in Table 2.
[0083] Specifically, the denitrification catalyst is ground, passed through an 80-100 mesh sieve, the catalyst powder is weighed, placed in a three-necked flask, KNO3 solution is added, stirred in a water bath at 80°C for 2 hours, then dried, and calcined in air at 550°C to obtain the product.
[0084] Specifically, the denitrification catalyst is placed in a fixed-bed reactor. An arsenic-containing solution is injected into a preheater via a peristaltic pump, where it is heated to form gaseous As2O3. An N2 / O2 mixture is used as a carrier gas to carry the gaseous As2O3 into the reactor, where it is deposited on the catalyst. By controlling parameters such as the concentration of the arsenic-containing solution, the peristaltic pump flow rate, and the preheater temperature, the loading of As2O3 on the catalyst is accurately achieved.
[0085] The SO2 / SO3 oxidation rate was tested according to the industry standard DL / T2279-2021 "Test Method for Sulfur Dioxide Oxidation Rate of Flue Gas Denitrification Catalysts in Thermal Power Plants (Powder Method)".
[0086] Table 2 Performance of Denitrification Catalysts
[0087]
[0088] In summary, the denitrification catalyst prepared by this invention exhibits good denitrification activity (up to 91.3%) with a flue gas temperature of 350℃ and a loading of 1.2% As2O3. The catalyst also shows good dioxin denitrification effect (up to 87.3%) at a flue gas temperature of 250℃, with a N2 selectivity of up to 99.6%. The As2O3 deposition on the catalyst surface after 120 hours is only 0.18%, demonstrating good resistance to arsenic poisoning and reducing As2O3 deposition on the catalyst surface.
[0089] The above detailed description is a specific description of one of the feasible embodiments of the present invention. This embodiment is not intended to limit the patent scope of the present invention. All equivalent implementations or modifications that do not depart from the present invention should be included within the scope of the technical solution of the present invention.
[0090] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A core-shell structured arsenic poisoning-resistant denitrification catalyst, characterized in that, The catalyst, comprising vanadium-molybdenum-holmium-zinc composite oxide particles as the core, silicon-cerium oxide as the inner shell, and titanium-phosphorus oxide as the outer shell, wherein the mass ratio of the core to the inner shell is (3-15):100, and the mass ratio of the core to the outer shell is (25-60):100, is prepared by the following steps: Step S1: Mix vanadium oxysulfate, ammonium molybdate, holmium sulfate, zinc sulfate and oxalic acid solution evenly to form solution A; place solution A in a high-pressure reactor lined with polytetrafluoroethylene, add dimethicone, and carry out hydrothermal reaction. After the reaction, the product is filtered, washed, vacuum dried and calcined to obtain vanadium-molybdenum-holmium-zinc composite oxide particles. Step S2: Vanadium-molybdenum-holmium-zinc composite oxide particles, acrylic vinyl pyridine copolymer, and deionized water are ultrasonically stirred for 12-24 hours to obtain suspension A. Suspension A is filtered to obtain activated vanadium-molybdenum-holmium-zinc composite oxide particles. Step S3: The activated vanadium-molybdenum-holmium-zinc composite oxide particles are ultrasonically dispersed in glycerol to form suspension B. The silicon-cerium sol is added to suspension B and ultrasonically dispersed for 2-6 hours to form suspension C. Urea solution is added dropwise to suspension C until a precipitate is formed. The solution is stirred evenly to obtain solution D under critical conditions. Step S4: Add propylene glycol block polyether type L-62 to titanium phosphate sol, add urea solution until a precipitate is formed in the solution, stir evenly, and obtain solution E under critical conditions; Step S5: Add solution E to solution D, stir evenly, and add to a high-pressure reactor lined with polytetrafluoroethylene for hydrothermal reaction. After the reaction, the product is filtered, washed, vacuum dried, and calcined to obtain a double-core-shell structured anti-arsenic poisoning denitrification catalyst.
2. The core-shell structured arsenic poisoning-resistant denitrification catalyst according to claim 1, characterized in that, The mass ratio of vanadium oxide, molybdenum oxide, holmium oxide, and zinc oxide in the vanadium-molybdenum-holmium-zinc composite oxide particles is 1:(2-10):(0.5-2):(0.1-1).
3. The core-shell structured arsenic poisoning-resistant denitrification catalyst according to claim 1, characterized in that, The mass ratio of silicon oxide to cerium oxide in the silicon-cerium oxide is 100:(1-10).
4. The core-shell structured arsenic poisoning-resistant denitrification catalyst according to claim 1, characterized in that, The mass ratio of titanium oxide to phosphorus oxide in the titanium-phosphorus oxide is 100:(0.1-3).
5. A method for preparing a core-shell structured arsenic poisoning-resistant denitrification catalyst according to any one of claims 1-4, characterized in that, Includes the following steps: Step S1: Mix vanadium oxysulfate, ammonium molybdate, holmium sulfate, zinc sulfate, and oxalic acid solution evenly to form solution A; Solution A was placed in a high-pressure reactor lined with polytetrafluoroethylene, and dimethicone was added to carry out a hydrothermal reaction. The product after the reaction was filtered, washed, vacuum dried and calcined to obtain vanadium-molybdenum-holmium-zinc composite oxide particles. Step S2: Vanadium-molybdenum-holmium-zinc composite oxide particles, acrylic vinyl pyridine copolymer, and deionized water are ultrasonically stirred for 12-24 hours to obtain suspension A. Suspension A is filtered to obtain activated vanadium-molybdenum-holmium-zinc composite oxide particles. Step S3: The activated vanadium-molybdenum-holmium-zinc composite oxide particles are ultrasonically dispersed in glycerol to form suspension B. The silicon-cerium sol is added to suspension B and ultrasonically dispersed for 2-6 hours to form suspension C. Urea solution is added dropwise to suspension C until a precipitate is formed. The solution is stirred evenly to obtain solution D under critical conditions. Step S4: Add propylene glycol block polyether type L-62 to titanium phosphate sol, add urea solution until a precipitate is formed in the solution, stir evenly, and obtain solution E under critical conditions; Step S5: Add solution E to solution D, stir evenly, and add to a high-pressure reactor lined with polytetrafluoroethylene for hydrothermal reaction. After the reaction, the product is filtered, washed, vacuum dried, and calcined to obtain a double-core-shell structured anti-arsenic poisoning denitrification catalyst.
6. The preparation method according to claim 5, characterized in that, In step S1, the concentration of oxalic acid is 1%-5%, and the mass ratio of vanadium oxysulfate to dimethicone is 1:(0.1-0.5).
7. The preparation method according to claim 5, characterized in that, In step S1, the hydrothermal reaction temperature is 150-200℃, the hydrothermal time is 6-15h, the drying temperature is 50-80℃, the drying time is 12-24h, and the calcination temperature is 500-650℃, with a calcination time of 2-6h.
8. The preparation method according to claim 5, characterized in that, In step S2, the mass ratio of vanadium oxide to vinylpyridine acrylate copolymer is 1:(0.1-0.5).
9. The preparation method according to claim 5, characterized in that, In step S4, the mass ratio of vanadium oxide to propylene glycol block polyether is 1:(0.6-1.2).
10. The preparation method according to claim 5, characterized in that, In step S5, the hydrothermal reaction temperature is 80-120℃ and the hydrothermal time is 8-12h; the drying temperature is 60-120℃ and the drying time is 24-48h; the calcination temperature is 450-600℃ and the calcination time is 3-8h.
Citation Information
Patent Citations
Fe-ZSM-5@Ce / meso-SiO2 denitration catalyst and preparation method thereof
CN108993579A
Low-cost NH3-SCR denitration catalyst and preparing method thereof
CN109395775A
Low-temperature alkali-resistant metal SCR denitration catalyst and preparation method and application thereof
CN111744468A
Preparation method of phosphorus-doped cerium-titanium selective catalytic reduction denitration catalyst
CN112044455A
Sulfur-dioxide-poisoning-resistant catalyst for treating nitrogen oxide-containing waste gas, waste gas treating agent and application of sulfur-dioxide-poisoning-resistant catalyst and waste gas treating agent
CN114042449A